UJI PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN TV BERBAYAR INDOVISION CABANG JEMBER - Ahmad Sauqi; Handriyono Handriyono (RELASI : JURNAL EKONOMI, 2013)
Experiment of the influence  of quality service on customers satisfaction and loyalty in a pay TV Indovision branch of Jember is intended to (1) test qualityinfluence services to the customers satisfaction. (2) test quality influence services to customers loyalty. (3) test the  influence of customers satisfacion to their loyailty. The Population in this study is all customers in a pay TV Indovision branch of Jember, meanwhile the target of this study is  exhaustive and active users of Indovision's service. Determination of sample size of 140 consumers ,conducted by Accidental Sampling. The method of analysis used in this study is structural equation. And results of analysis showed that quality services significantly ascendant to customers satisfaction, the quality services significantly ascendant to customers loyalty and signifantly ascendant satisfaction to loyalty of the customers. The influence of quality services to customers loyalty  have the most dominant factors  compared with the influence of quality services towards the customers satisfaction and satisfaction of influence of customers loyalty.